Mennonite Engagement with Iran (American Journal of Islam and Society, 2014)
The Mennonites relationship ongoing with Iran has developedover a period of more than twenty years. This essay traces the developmentof our relationships with Iranians and our program withIran, how it began with relief and reconstruction and progressedthrough a student exchange to an ongoing interfaith dialogue andvisiting scholars. The roles of several key Iranians, to whom muchcredit must be given, will also be discussed. The views expressedherein concerning the development of Mennonite engagementwith Iran are the personal views of the author and do not representthose of any Mennonite institution.